Synthesis, molecular structure and electrochemical properties of the star-shaped dinuclear complexes [Ru2(η6-p-Me–C6H4-iPr)2(μ2-S-p-C6H4–C4H3S)3]+ and [Rh2(η5-C5Me5)2(μ2-S-p-C6H4–C4H3S)3]+ - Chérioux, Frédéric; Therrien, Bruno; Sadki, Saïd; Comminges, Clément; Süss-Fink, Georg (My University, 2005)
The dinuclear cations [Ru2(η6-p-Me–C6H4–iPr)2(μ2-S-p-C6H4–Br)3]+ and [Rh(η5-C5Me5)(μ2-S-p-C6H4–Br)3]+ are found to undergo triple Suzuki coupling with 2- or 3-thiophene boronic acid to give [Ru2(η6-p-Me–C6H4–iPr)2(μ2-S-pC6H4–C4H3S)3]+ (1 and 2) and [Rh2(η5-C5Me5)2(μ2-S-p-C6H4–C4H3S)3]+ (3 and 4), respectively. The star-like complexes are potential precursors for the insertion of dinuclear organometallic entities in the main chain of conjugated molecules thanks to their free thienyl moieties at their periphery. The electrochemical and optical properties of these new complexes have also been investigated.
Keywords: Ruthenium; Rhodium; Complexes; Thiophene; Electrochemistry; UV–Vis